Determination of the fractions of syntrophically oxidized acetate in a mesophilic methanogenic reactor through an 12C and 13C isotope-based kinetic model. (1st October 2016) - Gehring, Tito; Niedermayr, Andrea; Berzio, Stephan; Immenhauser, Adrian; Wichern, Marc; Lübken, Manfred
Abstract: In order to accurately describe the carbon flow in anaerobic digestion processes, this work investigates the acetate degradation pathways through the use of stable carbon isotope analysis and a mathematical model. Batch assays using labeled 13 C acetate were employed to distinguish the acetate consumption through methanogenic Archaea and acetate-oxidizing Bacteria. Suspended and sessile biomass, with over 400 days of retention time, from a mesophilic (36.5 °C) upflow anaerobic filter was used as inocula in these assays. A three-process model for acetoclastic methanogenesis and syntrophic acetate oxidation (SAO) was developed to allow for a precise quantification of the SAO contribution. The model distinguishes carbon atoms in light and heavy isotopes, 12 C and 13 C, respectively, which permitted the simulation of the isotope ratios variation in addition to gas production, gas composition and acetate concentrations. The model indicated oxidized fractions of acetate between 7 and 18%. Due to the low free ammonia inhibition potential for the acetoclastic methanogens in these assays these findings point to the biomass retention times as a driven factor for the SAO pathway. The isotope-based kinetic model developed here also describes the δ 13 C variations in unlabeled assays accurately and has the potential to determine biological 13 C fractionation factors. Graphical abstract: Highlights: Acetate oxidation is relevant for a mesophilic Methanosaeta dominated reactor. Quantification of acetate degradation pathways based on δ 13 C analysis. Dynamic acetate degradation simulation including carbon isotopes differentiation. Independent metabolic pathway determination for suspended and biofilm biomass. Identifiability of 13 C fractionation factors through the developed kinetic model.